Refractory Ventricular Tachycardia From Coronary Vasospasm During Pregnancy - Ergle, Kevin (Ochsner J, 2019)
Background: Coronary vasospasm leading to variant angina is uncommon, and the condition is rare in pregnant patients. Many physiologic changes occur during pregnancy, but how these changes affect the spasticity of coronary arteries in patients predisposed to vasospasm is unknown. Vasospasm causing unstable arrhythmia from multiple foci can be difficult to treat. Case Report: A 22-year-old gravida 1 para 0 female at 17 weeks’ gestation with twins presented with chest pain refractory to sublingual nitroglycerin, ST segment elevation on electrocardiogram, and subsequent ventricular tachycardia requiring a shock by her implantable cardioverter defibrillator (ICD). The patient had a history of coronary vasospasm with ventricular arrhythmia that required placement of the ICD 5 years prior. Because of refractory symptoms, she required prolonged admission in the intensive care unit with high-dose intravenous nitroglycerin, calcium channel blockers, benzodiazepines, beta blockers, chemical sympathectomy, and intubation and sedation. Despite these measures, the patient continued to have vasospasm and ventricular tachycardia, so cesarean delivery and tubal ligation were performed. After delivery, she was rapidly weaned from all invasive treatment modalities and was discharged on oral nitrates and calcium channel blockers. Conclusion: To our knowledge, this case is the first report of severe drug-refractory vasospastic angina triggered by pregnancy. The hormonal and nervous system changes that occur during pregnancy appear to be a trigger for vasospasm, further highlighted by the quick resolution of the patient's symptoms postdelivery. A multidisciplinary approach for treatment of both mother and baby was necessary. Our case provides a cautionary tale that patients with refractory vasospastic angina may want to pursue definitive contraception.